CONCERNING EXPEDIENCY OF ADOPTING THE ECOLOGICAL CONSTITUTION OF THE EARTH - Tolkachova, Iryna; Kyrychenko, Victoriya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: analysis of issues of reforming the world’s ecological policy and research of problems that prevent the adoption of the Ecological Constitution of the Earth. Methods of research: in this article general scientific and special methods were used. So, the basis of research consists of methods of cognition (analysis, synthesis, induction, deduction, analogy, comparison, etc.), general scientific methods (empirical research, methods of theoretical cognition). Results: the Ecological Constitution of the Earth must be adopted, because it is important for everyone in the world, since the UN can create the conditions for cohesion and persuasion of states to adopt this Constitution and ensure the human right to a safe environment. The process of adopting the Ecological Constitution of the Earth cannot be postponed because time is running out, states do not always pay attention to violations of ecological human rights, and chances of correcting the situation are decreasing day by day. Therefore, the state’s ecological policy should be ensured at the international level by the Constitution and regulatory bodies, which will increase its effectiveness. Today, the planet Earth is completely in the hands of mankind, transnational corporations, for the sake of superprofits, can destroy the Earth’s biosphere and only caring people can save it. The Ecological Constitution of the Earth should become not just another international treaty, but a turning point in the evolution of society and start a new vision of the world, where man is not the centre of everything happening on the Earth, but nature, which includes man and all living and non-living things on the Planet as a whole. The idea of the Ecological Constitution of the Earth is variously developed at the theoretical level by domestic lawyers-ecologists, all scientific developments demand only the willful decision of the states of the world for their realization. The Ecological Constitution of the Earth is a complex international act that requires major changes that are worthwhile for people to live on the Earth. In order to save the Earth’s biosphere, it is necessary to change man’s attitude to nature and carefully use the natural resources that provide life on the Planet (air, water, forests). The right to a safe environment is one of the most important human rights today. The life and health of each of us depend on its realization. The problem of realization of the right to a safe environment is global today, and therefore needs the attention of the entire international community. Discussion: problems and prospects of adopting the Ecological Constitution of the Earth.